Implementasi Teori Belajar Kontruktivistik Dalam Pembelajaran IPA Kelas III di Madrasah Ibtidaiyah Islamiyah Lumajang - Hasanah, Fadilatul (IJIT: Indonesian Journal of Islamic Teaching, 2023)
This study aims to clearly describe the implementation of constructivistic theory in Madrasah Ibtidaiyah Islamiyah Lumajang. The approach used in this research is a qualitative approach, with the type of case study. Data collection techniques using observation, interviews and documentation. Determination of research subjects using purposive. Data collection techniques through observation, interviews and documentation. The data analysis used is the field data analysis model of Miles, Huberman and Saldana which includes data reduction, data display, and conclusion drawing / verification. Data validity uses triangulation of sources and techniques. The planning of constructivistic theory in learning IPA class III is carried out by teachers by determining the learning syllabus, Learning Implementation Plan (RPP) and determining learning media that are relevant to constructivistic theory, 2. The implementation of constructivistic theory in class III science learning includes preliminary activities, core activities which contain five stages, namely introduction, exploration, restructuring, application, review and evaluation, and closing activities, 3. Evaluation of constructivistic theory in class III science learning refers to affective aspects using attitude assessment, cognitive aspects using written assessments in the form of descriptions, psychomotor aspects using performance assessments.